Predictors of Medication Adherence in Pediatric Inflammatory Bowel Disease Patients at the Stollery Children's Hospital. (2009) - Kitney, L; Turner, JM; Spady, D; Malik, B; El-Matary, W; Persad, R; Huynh, HQ
Abstract : BACKGROUND: Patients with inflammatory bowel disease (IBD) often do not take their medications as prescribed. OBJECTIVE: To examine self-reported adherence rates in IBD patients at the Stollery Children's Hospital (Edmonton, Alberta) and to determine predictors of medication adherence. METHODS: A survey was mailed to 212 pediatric IBD patients of the Stollery Children's Hospital. A chart review was completed for those who returned the survey. RESULTS: A total of 119 patients completed the survey. The nonresponders were significantly older than responders (14.5 years versus 13.2 years; P=0.032). The overall adherence rate was 80%. Nonadherence was associated with older age (14.6 years versus 13.0 years; P=0.04), longer disease duration (5.0 years versus 3.1 years; P=0.004) and reported use of herbal medications (40.0% versus 13.6%; P=0.029). The most common reasons reported for missing medications were forgetfulness, feeling better and too many medications. In addition, patients reported being more likely to take anti-inflammatory medications and less likely to take herbal medicines. CONCLUSION: Identified predictors of nonadherence such as age, disease duration and use of herbal treatments may enable the development of specific strategies to improve adherence in adolescents with IBD.